2013
DOI: 10.3393/ac.2013.29.5.192
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Additional Four-Week Chemotherapy With Capecitabine During the Resting Periods After Six-Week Neoadjuvant Chemoradiotherapy in Patients With Locally Advanced Rectal Cancer

Abstract: PurposeThe aim of this study is to evaluate the efficacy and the safety of additional 4-week chemotherapy with capecitabine during the resting periods after a 6-week neoadjuvant chemoradiotherapy (NCRT) in patients with locally advanced rectal cancer.MethodsRadiotherapy was delivered to the whole pelvis at a total dose of 50.4 Gy for 6 weeks. Oral capecitabine was administered at a dose of 825 mg/m2 twice daily for 10 weeks. Surgery was performed 2-4 weeks following the completion of chemotherapy.ResultsBetwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In a previous study, Lee et al [ 35 ] showed that 4 additional weeks of neoadjuvant chemotherapy with capecitabine was safe during the resting periods before the surgery, but it did not improve the tumor response rate compared to conventional chemoradiation. A standard period of conventional neoadjuvant therapy consists of 5-6 weeks of concurrent chemoradiation, followed by a 6- to 8-week recovery window and then by a surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Lee et al [ 35 ] showed that 4 additional weeks of neoadjuvant chemotherapy with capecitabine was safe during the resting periods before the surgery, but it did not improve the tumor response rate compared to conventional chemoradiation. A standard period of conventional neoadjuvant therapy consists of 5-6 weeks of concurrent chemoradiation, followed by a 6- to 8-week recovery window and then by a surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, authors report that they tried an additional four weeks of chemotherapy with capecitabine during resting periods. They did not obtain a visibly better result; nonetheless, this article bears prospective meanings [ 1 ].…”
mentioning
confidence: 99%